Gender, symbols and traditional peacebuilding among the Nanka-Igbo people of Southeastern Nigeria (2007)
Women's class condition in modern Igboland (southeastern Nigeria) in particular and African society generally, which is characterized by her peripherialization in the scheme of state building and knowledge production, has led to the need for the re-examination of her cultural representation in specific cultural contexts in Africa prior to the major historical events (partition and colonization) in the continent, which led to pragmatic shift in local paradigms not just culturally, but also in the significance placed on the agencies of cultural transmission. This exercise has become imperative in order to make, if possible, an accurate (or near accurate?) representation of women in specific cultural situations. This article re-examines the perception that women have nothing to do with two key peace symbols - 'oji (kolanut) and 'ofo' (staff of authority and justice) - in Igbo culture as has been presented in the literature on lgbo culture. Using a case study typology, the study uses Nanka in Anambra State, south-eastern Nigeria as the study area. It identifies the place of the Earth goddess in 'oji and 'ofo' ritual performances and concludes that gender is mainstreamed in the usages of 'oji and 'ofo'.